Aesthetic and Functional Outcomes of Primary Hypospadias Repair: A Singlecentre Prospective Interventional Study - Tibar Banerjee; Anirban Basu; Sudipta Bera; Souvik Adhikari (Journal of Clinical and Diagnostic Research, 2024)
Introduction: The results of hypospadias repair are often marred by a high rate of complications. The contemporary hypospadias repair aims to reduce the complications with the utilisation of plastic and urogenital surgical principles. However, the aesthetic and functional outcomes are often less emphasised. Aim: To evaluate the functional and aesthetic outcomes related to the clinical grades of hypospadias and different surgical methods used for hypospadias repair. Materials and Methods: In this single-centre prospective interventional study, a total of 50 patients were operated on for hypospadias and studied between March 2020 and October 2021 at the Department of Burn and Plastic Surgery, IPGMER and SSKM, Kolkata, West Bengal, India. The severity of hypospadias was assessed with the Glans-Meatus-Shaft (GMS) score. The postoperative aesthetic and functional outcomes were evaluated with the Penile Perception Score (PPS) and Hypospadias Objective Scoring Evaluation (HOSE), respectively. The tabulated data were analysed with Statistical Package for the Social Sciences (SPSS) software (Version 29.0.2.0 Armonk, NY: IBM Corp). The subgroups within the population were compared with the Student’s t-test and a p-value <0.05 was considered statistically significant. Results: The mean age of the study population was 9.92±8.61 years, ranging from one year to 34 years. The mean GMS score was 6.8±2.33. The mean PPS and HOSE scores were 7.62 (SD 1.5) and 11.6 (SD 1.96), respectively. A 72% of patients had a satisfactory outcome of PPS score (6-9), which is mostly obtained in distal hypospadias cases (25/50). There were significant differences in PPS score (p=0.008*) and HOSE score (p=0.012*) between cases with no chordee and those with severe chordee, but not among other groups based on the severity of chordee. There were significant differences in the PPS score (p=0.002*) and HOSE Score (p=0.035*) were observed between granular and perineal hypospadias. There was significant difference in the PPS score between the procedures for proximal and distal hypospadias group, but not between the procedures within each group. Conclusion: The chance of obtaining a better aesthetic outcome depends on the lesser severity of the chordee and a distal location of the meatus. The location of meatus, rather than the type of surgery, remains the most important factor influencing both the aesthetic and functional outcome. Use of an intermediate layer with the Dartos flap and Tunica Vaginalis (TV) flap may improve the functional outcome of the surgery. However, this finding needs further larger sample analysis and randomised controlled analysis to draw a strong conclusion.